The prognostic significance of serum lactate dehydrogenase-to-albumin ratio in colorectal cancer - Aday, Ulaş (Ann Surg Treat Res, 2020)
PURPOSE: The purpose of our study was initially to explore the prognostic role of LDH-to-albumin ratio in patients with colorectal carcinoma (CRC) undergoing curative resection. METHODS: The retrospective study included 295 CRC patients that underwent curative resection. According to time-dependent receiver operating characteristics (ROC) analysis, the optimal cutoff value for pretreatment LDH-to-albumin ratio was 52.7. Cox regression univariate and multivariate analyses were utilized to analyze the prognostic factors for disease-free survival (DFS) and overall survival (OS). RESULTS: The 295 participants included 117 women (39.7%) and had an overall mean age of 55.8 ± 14.1 years. The median follow-up period was 31.8 ± 21 months (range, 6–78 months) and 53 patients (18.0%) died from cancer during the follow-up period. The 5-year DFS and OS rates were 65.4% and 68.5% in patients with LDH-to-albumin ratio <52.7 (n = 152), and were 55.2% and 55.4% in patients with LDH-to-albumin ratio ≥52.7 (n = 143), respectively. Kaplan-Meier curves showed that LDH-to-albumin ratio ≥52.7 was significantly associated with worse DFS and OS (P = 0.003 and P < 0.001, respectively). Multivariate analyses revealed that LDH-to-albumin ratio was an independent predictor of resectable CRC (odds ratio, 2.104; 95% confidence interval, 1.112–3.982; P = 0.022). CONCLUSION: Our study revealed that high pretreatment LDH-to-albumin ratio level was an unfavorable prognosticator in patients with CRC undergoing curative resection. LDH-to-albumin ratio is a candidate to be a prognostic biomarker in clinical practice.